2017
DOI: 10.3892/br.2017.1017
|View full text |Cite
|
Sign up to set email alerts
|

Expression of doublecortin and CaM kinase‑like‑1 protein in serrated neoplasia of the colorectum

Abstract: Abstract. The adenoma-carcinoma sequence (ACS) and the serrated pathway are two distinct developmental routes leading to the formation of colorectal carcinoma. Recently, the doublecortin and CaM kinase-like-1 protein (DCLK1) has been reported to serve as an intestinal cancer stem cell marker and has been demonstrated to be overexpressed through the ACS; however, there is a lack of reports on the role of DCLK1 in the serrated pathway. To clarify the correlation between DCLK1 protein expression and clinicopathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…The group reported that sinonasal polyp derived cultures from both submerged epithelia (nondifferentiated) and cultures with biphasic epithelia (air-liquid interface) produced IL-25 after stimulation with IL-13, possibly suggesting that differentiation does not need to occur completely in order for IL-25 production to occur. Indeed, populations of DCAMKL1-positive cells are increased in human serrated colorectal polyps 73 and nonesmall cell lung cancer 74 and have been studied for its prospective role in the epithelial-to-mesenchymal transition. 75 Together, high concentrations of tuft cells or tuft cell-progenitor cells coupled with persistent epithelial barrier perturbation may be important roles in the origination of type 2 inflammation in the upper airway.…”
Section: Tuft Cells Are Enriched In Human Nasal Polyp Tissuementioning
confidence: 99%
“…The group reported that sinonasal polyp derived cultures from both submerged epithelia (nondifferentiated) and cultures with biphasic epithelia (air-liquid interface) produced IL-25 after stimulation with IL-13, possibly suggesting that differentiation does not need to occur completely in order for IL-25 production to occur. Indeed, populations of DCAMKL1-positive cells are increased in human serrated colorectal polyps 73 and nonesmall cell lung cancer 74 and have been studied for its prospective role in the epithelial-to-mesenchymal transition. 75 Together, high concentrations of tuft cells or tuft cell-progenitor cells coupled with persistent epithelial barrier perturbation may be important roles in the origination of type 2 inflammation in the upper airway.…”
Section: Tuft Cells Are Enriched In Human Nasal Polyp Tissuementioning
confidence: 99%
“…This attribute correlated with increased pluripotency and self-renewal ability of cancer cells (21,22). However DCLK1 expression was infrequently detected in serrated tumors of the colorectum (23).…”
mentioning
confidence: 96%
“…35 Herein, we highlighted a mechanism linking a CSCs maker DCLK1 and 5-fluorouracil resistance, and demonstrated that DCLK1 inhibitor suppressed 5-fluorouracil resistant CRC cells through inhibiting CCAR1/β-catenin pathway-mediated cancer stemness. Accumulating evidences showed that DCLK1 was overexpressed in several types of tumours, especially in CRC [9][10][11][12][13][14][15] and pancreatic cancer. 16,17 Besides, elevated levels of DCLK1 were closely correlated with poor outcomes and tumour recurrence and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidences showed that DCLK1 was overexpressed in several types of tumours, especially in CRC [9][10][11][12][13][14][15] and pancreatic cancer. 16,17 And elevated levels of DCLK1 were closely correlated with poorer outcomes and higher rates of tumour recurrence and metastasis.…”
Section: Dclk1 Is Correlated With 5-fluorouracil Resistance In Crcmentioning
confidence: 99%
See 1 more Smart Citation